2016
DOI: 10.1111/cas.12882
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐dependent cellular cytotoxicity toward neuroblastoma enhanced by activated invariant natural killer T cells

Abstract: Anti‐ganglioside GD2 antibodies mainly work through antibody‐dependent cellular cytotoxicity (ADCC) and have demonstrated clinical benefit for children with neuroblastoma. However, high‐risk neuroblastoma still has a high recurrence rate. For further improvement in patient outcomes, ways to maximize the cytotoxic effects of anti‐GD2 therapies with minimal toxicity are required. Activated invariant natural killer T (iNKT) cells enhance both innate and type I acquired anti‐tumor immunity by producing several kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Additional blockade of PDL1 expressed on tumor cell lines resulted in enhanced direct cytotoxicity of the stimulated iNKT cells. Since iNKT cells are reported to not directly exhibit antibody-dependent cellular cytotoxicity (ADCC) [35], we concluded that PDL1 blockade enhances cytotoxic functions of iNKT cells. In addition, we found that anti-PDL1 antibody only improved Th1 cytokine production, whereas PDL2 blockade appeared to increase IL-4 secretion.…”
Section: Discussionmentioning
confidence: 98%
“…Additional blockade of PDL1 expressed on tumor cell lines resulted in enhanced direct cytotoxicity of the stimulated iNKT cells. Since iNKT cells are reported to not directly exhibit antibody-dependent cellular cytotoxicity (ADCC) [35], we concluded that PDL1 blockade enhances cytotoxic functions of iNKT cells. In addition, we found that anti-PDL1 antibody only improved Th1 cytokine production, whereas PDL2 blockade appeared to increase IL-4 secretion.…”
Section: Discussionmentioning
confidence: 98%
“…Different from CD56+ T cells, we found iNKT expressed less CD16 than CD56+ T cells and failed to response to Ab-coated P815 cells, indicating that iNKT was unable to mediate ADCC responses though shared some NK characteristics. Another study has also found that iNKT cells did not mediated killing of neuroblastoma cell lines in the presence of a relevant antibody, although ADCC of mediated by NK cells was enhanced by activated iNKT cells [38]. CD56+ T cells were heterozygous cell population and could be subdivided into CD4+, CD8+, and DN subsets.…”
Section: Discussionmentioning
confidence: 99%
“…NLF cells also have low GD2 expression and high metastatic ability. 35 Moreover, NLF cells, like many high-risk NBs, may induce a tolerogenic immune environment due to their significant immunosuppressive activity, mainly based on inhibition of dendritic cell differentiation and activation. 36…”
Section: Introductionmentioning
confidence: 99%